Human-Computer Interaction, Tourism and Cultural Heritage : First International Workshop, HCITOCH 2010 Brescello, Italy, September 7-8, 2010 Revised Selected Papers / Francisco V. Cipolla Ficarra...[et] - Kratky, Andreas Eds
Constitutes the refereed proceedings of the First International Workshop on Human-Computer Interaction, Tourism and Cultural Heritage, HCITOCH 2010, held in Brescello, Italy, in September 2010.